Fever of Unknown Origin due to Liver Tuberculosis - Irman Firmansyah; Joko Jong; Noorwati Noorwati; Leo Nainggolan (The Indonesian Society for Digestive Endoscopy, 2003)
Infection, especially extra pulmonary tuberculosis, remain the leading cause of fever of unknown origin (FUO). FUO is defined as temperature higher than 38.3 ºC with duration of fever of more than 3 weeks. We reported a case of liver tuberculosis, whose had fever more than 38.3 ºC in 2 months. A liver biopsy and histology evaluation have performed revealing liver tuberculosis. The patient received oral anti-tuberculosis agents. But after three days of anti-tuberculosis treatment, the patient experience jaundice. The patient was diagnosed as a drug induced hepatitis. After adjusted regimen of oral anti- tuberculosis, the patient’s condition improved. The patient was back home with good conditions. Keywords: fever of unknown origin - liver tuberculosis.